Structural Equation Modeling in Purchasing Decision : Study Case of Mixue Ice Cream and Tea - Walean, Ronny Hansje; Tangkudung, Elisabeth Fransisca (PT Mattawang Mediatama Solution, 2024)
In the era of increasingly fierce market competition, a deep understanding of the factors that influence consumer purchasing decisions is key to the success of a company or business actor. This study aims to investigate the effect of positioning, price perception, and brand image on customer satisfaction and its impact on purchasing decisions for Mixue Ice Cream and Tea consumers. The research method used is descriptive quantitative, collecting primary data through questionnaires distributed to respondents and using secondary data as support. The population of this study was Mixue Ice Cream and Tea consumers, with a sample of 270 respondents selected using a purposive sampling method. The data were analyzed using the smartPLS version 4.0 program to obtain respondents' descriptions, data frequency distribution, outer and inner model test results, determination, and hypotheses. The analysis results show that positioning, price perception, and brand image have a significant effect on customer satisfaction by 75%. Based on the study's results, the three exogenous variables, namely positioning, price perception, and brand image, and one intervening variable, namely customer satisfaction, have a significant effect on the endogenous variable, namely purchasing decisions by 73% with a significance level of α = 5%. Through this research, it provides significant insight for business people in paying attention to the quality of products or services to attract consumer attention and satisfaction, so that a perception of positioning is formed in the minds of consumers and can increase retention of purchasing decisions.